The Role of PPAT in the Registration Process for the Transfer of Land Rights based on Buying and Selling Transaction - Fatoni Winahyu; Sri Kusriyah (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to determine and analyze about the role of PPAT in the registration process for the transfer of land rights based on buying and selling in Pati Regency. The research approach method used in this thesis is a sociological juridical approach. The specification of this research is analytical descriptive, a study that tries to describe the problems that occur in practice in the field associated with other provisions and then analyzed to obtain supporting facts and inhibiting factors of the problems studied. The data sources of this research consist of primary data and secondary data. Methods of collecting data using interviews, document studies, field studies.The data obtained from both field studies and document studies are basically data that were analyzed descriptively qualitatively. The results showed thatThe deed made by PPAT acts as an authentic deed, one of which is the deed of sale and purchase (AJB), which is a deed made when someone wants to sell their land to someone else. AJB functions to take care of the letters of transition from the old owner to the new owner. Before making the AJB, PPAT checks the authenticity of the certificate to the land office. The making of AJB is attended by sellers, prospective buyers, and at least two witnesses. AJB is made if the sale and purchase transaction has been paid off. According to the Decree of the State Minister of Public Housing Number 9 of 1995 concerning Guidelines for Binding the Sale and Purchase of Houses; AJB must be signed by the buyer and seller before the PPAT if the buyer has paid the entire land price along with taxes and other costs related to the sale and purchase transaction.